Medication Management Performance in Parkinson's Disease: Examination of Process Errors. (24th February 2021) - Sumida, Catherine A; Lopez, Francesca V; Van Etten, Emily J; Whiteley, Nicole; Moore, Raeanne C; Litvan, Irene; Lessig, Stephanie; Gilbert, Paul E; Schmitter-Edgecombe, Maureen; Filoteo, J Vincent; Schiehser, Dawn M
Abstract: Objective: Individuals with Parkinson's disease (PD) are at risk for increased medication mismanagement, which can lead to worse clinical outcomes. However, the nature of the errors (i.e., undertaking or overtaking medications) contributing to mismanagement and their relationship to cognition in PD is unknown. Therefore, this study sought to examine errors committed on the Medication Management Ability Assessment (MMAA) between PD participants with normal cognition (PD-NC) or mild cognitive impairment (PD-MCI) relative to healthy adults (HA). Method: HA (n = 74), PD-NC (n = 102), and PD-MCI (n = 45) participants were administered the MMAA to assess undertaking, overtaking, and overall errors as well as overall performance (total score). Additionally, participants were administered a comprehensive neuropsychological battery from which cognitive composites of Attention, Learning, Memory, Language, Visuospatial, and Executive Functioning were derived. Results: Separate negative binomial regression analyses indicated the PD-MCI group performed significantly worse overall on the MMAA (total score) and committed more undertaking and overall errors relative to HA and PD-NC. In the PD-MCI group, poorer MMAA performance was associated with worse delayed memory performance, whereas cognitive performance was not related to MMAA in HA or PC-NC. Conclusion: Compared to PD and healthy adults with normal cognition, PD-MCI patients exhibited greater difficulty with medication management, particularly with undertaking medications. Poorer medication management in PD-MCI was associated with worse delayed recall. Thus, PD-MCI patients experiencing memory problems may require additional assistance with their medications. Findings have clinical relevance suggesting that objective measures of medication errors may assist clinicians in identifying PD patients needing adherence strategies.